2019
DOI: 10.4103/ijd.ijd_111_18
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and dyslipidemia among Nigerians with lichen planus: A cross-sectional study

Abstract: Background: Lichen planus (LP) is an inflammatory skin disease of unknown etiology associated with chronic inflammation, oxidative stress induction, and cardiovascular risk factors. Objectives: To document the prevalence of metabolic syndrome (MetS), dyslipidemia, and associated factors in Nigerian patients with LP. Methods: A cross-sectional design was made to evaluate 90 patients with LP and 90 controls for MetS and dyslipidemia in two Nige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Lichen planus (LP) is another chronic inflammatory skin disease; it affects about 1% of the population [ 21 ]. It has been suggested that LP may be genetically determined and an autoimmune disorder.…”
Section: Lichen Planusmentioning
confidence: 99%
See 1 more Smart Citation
“…Lichen planus (LP) is another chronic inflammatory skin disease; it affects about 1% of the population [ 21 ]. It has been suggested that LP may be genetically determined and an autoimmune disorder.…”
Section: Lichen Planusmentioning
confidence: 99%
“…The majority of available studies suggest an increased risk of MS in LP subjects. The estimated frequency is distributed from 6% to 77% [ 21 ]. There have been several studies thus far in which there was a higher prevalence (significantly or insignificantly) of MS in LP patients [ 25 , 26 , 27 , 28 ].…”
Section: Lichen Planusmentioning
confidence: 99%